3x . 3 = 243
7 . 2x = 56
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) Ta có 2x + 2x + 1 + 2x + 2 = 56
⇒ 2x ( 1 + 21 + 22 ) = 56
⇒ 2x . 7 = 56
⇒ 2x = 56 : 7 = 8 = 23
Vậy x = 3
b) Ta có 3x + 3x + 2 + 3x + 3 = 111
⇒ 3x ( 1 + 32 + 33 ) = 111
⇒ 3x . 37 = 111
⇒ 3x = 111 : 37 = 3 = 31
Vậy x = 1
a, 3 x + 1 : 3 4 = 81
3 x - 3 = 3 4
x – 3 = 4
x = 7
Vậy x = 7
b, 3 x + 3 . 3 x + 1 = 729
3 2 x + 4 = 3 6
2x + 4 = 6
x = 1
Vậy x = 1
c, 2 x + 3 . 2 x = 128
2 2 x + 3 = 2 7
2x + 3 = 7
x = 2
Vậy x = 2
d, 23 + 3 x = 5 6 : 5 3
23 + 3 x = 5 3
23 + 3x = 125
3x = 102
x = 34
Vậy x = 34
e, 2 x + 2 x + 4 = 272
2 x + 2 x . 2 4 = 272
2 x ( 1 + 2 4 ) = 272
2 x . 17 = 272
2 x = 16
2 x = 2 4
x = 4
Vậy x = 4
4:
=>(2x+3,5)=7/12*3/14=21/168=1/8
=>2x=1/8-7/2=1/8-28/8=-27/8
=>x=-27/16
5: =>1/3:3x=-21/4
=>3x=-1/3:21/4=-1/3*4/21=-4/63
=>x=-4/189
6: =>2+7/9-3/4(x+1)=7/9
=>2-3/4(x+1)=0
=>3/4(x+1)=2
=>x+1=2:3/4=2*4/3=8/3
=>x=5/3
a) \(-45:5.\left(-3-2x\right)=3\)
\(-9.\left(-3-2x\right)=3\)
\(-3-2x=\left(3:-9\right)\)
\(-3-2x=\dfrac{-1}{3}\)
\(-2x=-3-\dfrac{1}{3}\)
-2x=\(\dfrac{-10}{3}\)
\(x=\dfrac{-10}{3}:-2\)
\(x=\dfrac{5}{3}\)
b)
3x - 28 = x + 36
<=> 3x - x = 36 + 28
<=> 2x = 64
<=> x = 32
Vậy x = 32
c)
(-12)2.x = 56 + 10.13.x
144.x = 56 + 130.x
144x – 130 x = 56
14x = 56
x = 56: 14
x = 4
Vậy x = 4
100+2x+3x+x/2-56=66
<=> 2x+3x+x/2=66+56-100
<=> 5x+x/2= 22
<=> 5x+0,5x=22
<=>5,5x=22
<=>x= 4
a)
1 5 27 + 3 x − 7 9 3 = 24 27 3 x − 7 9 3 = 24 27 − 1 5 27 3 x − 7 9 3 = − 8 27 3 x − 7 9 = − 2 3 3 x = 1 9 x = 1 27
b)
2 x − 1 2 = 3 4 2 x = 5 4 x = 5 8 x = ± 5 8
c)
2 x − 1 3 + 5 6 = 1 2 x − 1 3 = 1 6 2 x − 1 3 = ± 1 6
TH1:
2 x − 1 3 = 1 6 2 x = 1 2 x = 1 4
TH2:
2 x − 1 3 = − 1 6 2 x = 1 6 x = 1 12
Vậy x = 1 4 hoặc x = 1 12
a.
\(10-2\left(4-3x\right)=-4\)
\(\Leftrightarrow2\left(4-3x\right)=10+4\)
\(\Leftrightarrow2\left(4-3x\right)=14\)
\(\Leftrightarrow4-3x=7\)
\(\Leftrightarrow3x=-3\)
\(\Leftrightarrow x=-1\)
b.
\(-12+3\left(-x+7\right)=-18\)
\(\Leftrightarrow3\left(-x+7\right)=-18+12=-6\)
\(\Leftrightarrow-x+7=-6:3=-2\)
\(\Leftrightarrow x=9\)
c.
\(-45:5.\left(-3-2x\right)=3\)
\(\Leftrightarrow-9.\left(-3-2x\right)=3\)
\(\Leftrightarrow-3-2x=-\dfrac{1}{3}\)
\(\Leftrightarrow2x=-\dfrac{8}{3}\)
\(\Leftrightarrow x=-\dfrac{4}{3}\notin Z\left(loại\right)\)
Câu này em ghi sai đề?
d.
\(3x-28=x+36\)
\(\Leftrightarrow2x=28+36\)
\(\Leftrightarrow2x=64\)
\(\Leftrightarrow x=32\)
e.
\(\left(-12\right)^2.x=56+10.13x\)
\(\Leftrightarrow144x=56+130x\)
\(\Leftrightarrow144x-130x=56\)
\(\Leftrightarrow14x=56\)
\(\Leftrightarrow x=4\)
a ) 3x . 3 = 243
3x = 243 : 3
3x = 81
3x = 34
=> x = 4
Vậy x = 4
b ) 7 . 2x = 56
2x = 56 : 7
2x = 8
2x = 23
=> x = 3
Vậy x = 3
3x.3 = 243
3x = 243 : 3
3x = 81
3x = 3.3.3.3
x = 4
7.2x = 56
2x = 56 : 7
2x = 8
2x = 2.2.2
2x = 23
x = 3